2023
DOI: 10.1002/apxr.202200055
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Surface Energy and Surface/Interface Stress Effects in Spin Crossover Nanomaterials

Abstract: Understanding phase transformation processes at the nanoscale is an important step for the integration of phase change materials into functional nanodevices. Here, a numerical method to assess surface energy and surface stress contributions to finite size effects in spin crossover nanomaterials is proposed. Starting from their formal definitions, molecular dynamic simulations combined with continuum mechanics and thermodynamic considerations on model thin films are performed. The surface energy values extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…In the interim, we used molecular dynamics (MD) simulations, based on a recently built force field, to calculate the surface energies of the compound [Fe(pyrazine)][Ni(CN) 4 ] in the two spin states. 33,52 (see the ESI† for more details of the MD calculation.) Through these calculations, the obtained surface energies in the LS and HS states are E LS sur = 49 mJ m −2 and E HS sur = 21 mJ m −2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the interim, we used molecular dynamics (MD) simulations, based on a recently built force field, to calculate the surface energies of the compound [Fe(pyrazine)][Ni(CN) 4 ] in the two spin states. 33,52 (see the ESI† for more details of the MD calculation.) Through these calculations, the obtained surface energies in the LS and HS states are E LS sur = 49 mJ m −2 and E HS sur = 21 mJ m −2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“… 29 Owing to the large volume misfit between HS and LS molecules, one can expect that this parameter also plays a crucial role in SCO nanometerials. 33 …”
Section: Introductionmentioning
confidence: 99%
“…−8 mJ m −2 ) due to dangling bonds led to a reduction of 4−5 K in the transition temperature and accommodating the interfacial stress led to a reduction of ∼10 K in transition temperature in the thin-film slab. 70 The fabrication of robust thin films on various substrates remains crucial from the perspective of device applications. Various methods, such as spin coating, drop casting, and Langmuir−Blodgett techniques, have been used to deposit thin films.…”
Section: Sco Nanoparticle and Thin-film Toward Device Applicationsmentioning
confidence: 99%
“…Further, by utilizing molecular dynamics simulations with thermodynamic considerations on model thin films, it was found that the surface energy difference between HS and LS states ( ca . −8 mJ m –2 ) due to dangling bonds led to a reduction of 4–5 K in the transition temperature and accommodating the interfacial stress led to a reduction of ∼10 K in transition temperature in the thin-film slab …”
Section: Sco Nanoparticle and Thin-film Toward Device Applicationsmentioning
confidence: 99%